EFFECTS OF ELECTRIC FIELD AND IMAGE CHARGES ON THE IMPURITY-RELATED OPTICAL ABSORPTION COEFFICIENTS IN A SPHERICAL QUANTUM DOT - Vartanyan, A.L.; Asatryan, A.L.; Mkrtchyan, A.A.; Avetisyan, S.S.; Kirakosyan, A.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
The influence of an image charge effect on the impurity-related energies, the oscillator strengths of transitions from the 1s-like state to 2px and 2pz states as well as the optical absorption coefficients in a spherical quantum dot in the presence of an external electric field have been studied. The results show that the image charges lead to significant changes in the optical coefficients of the system.